Reduction of inter- and intraspecific seed mass variability along a land-use intensification gradient. (October 2021) - Bazzato, Erika; Serra, Elisa; Maccherini, Simona; Marignani, Michela
Highlights: Land-use intensity gradient affects seed mass for two common Mediterranean species. Inter and intraspecific seed mass variability is reduced in urban and artificial areas. Same environmental drivers can affect seed mass with opposite trends. The ecological value of small isolated patches depends also by the land-use type. Abstract: The functional response of natural patches to surrounding land-use changes is strongly related to variations in functional traits of coexisting species. To exemplify the effects on species of a general pattern of land-use intensification mountains-coastland, we investigated the variation of a key plant trait - seed mass - in small woodlots located along a land-use intensification gradient for two common species ( Asparagus albus and Asparagus acutifolius ) in the Mediterranean areas. Moreover, along this gradient, we also explored the relationship between seed mass variation and different environmental filters. Along the gradient, A. acutifolius seed mass decreased from natural and semi-natural to urban and artificial areas (higher to lower elevation), whereas A. albus seed mass increased along the same gradient, with heavier seed in patches located in the urban and artificial areas than in those located in natural and semi-natural areas. At intra-specific level, A. acutifolius seeds were significantly different at the extremes of the gradient (natural and semi-natural vs urban and artificial areas), while A. albus showed significant differences both between natural and semi-natural areas and urban and artificial areas, and between agricultural and urban and artificial areas, revealing more sensitiveness to land-use change. The land-use type influenced seed mass variability: in the small patches located in natural and semi-natural areas and in agricultural ones, we observed for both species a higher seed mass variability, being highest in the agricultural areas, while we observed a limited variability in urban and artificial areas, suggesting a homogenization in terms of seed mass within and across species in human-altered areas. Environmental drivers on the seed mass of the two species showed an opposite trend in relation to biotic, topographic and bioclimatic variables. We observed that for two common Mediterranean species, land-use type influenced one of the most important plant functional traits (i.e., seed mass), leading to a reduction of intraspecific variability in artificial context. Understanding how and why these relations occur could improve our capacity to find adaptive strategies for environmental management.